A new concept of Absoloniella (=Ruffodytes syn. n.) for five blind Mediterranean species (Coleoptera: Brachyceridae: Erirhininae) - Grebennikov, Vasily V. (Zootaxa, 2014)
A hundred year-long taxonomic ambiguity surrounding two mysterious species originally described as Caulomorphus reitteri Müller, 1912 and Absoloniella cylindrica Formánek, 1913, both known from single specimens believed to be lost, is resolved. This is achieved by designation of their neotypes based on the same specimen collected together, and considered conspecific, with the holotype of Ruffodytes hellenicus Osella, 1973, the latter the type of the genus Ruffodytes Osella, 1973. This action triggers the following nomenclatorial and taxonomic changes: (1) the generic name Ruffodytes Osella, 1973 syn. n. is a junior subjective synonym of Absoloniella Formánek, 1913; (2) the names cylindrica syn. n. and hellenica syn. n. are junior objective and subjective synonyms, respectively, of the name reitteri for the species Absoloniella reitteri (Müller, 1912); (3) the genus Absoloniella currently comprises five species: A. reitteri (Müller, 1912), A. italica (Osella, 1976) comb. n., A. pacei (Osella, 1976) comb. n., A. servadeii (Osella, 1982) and A. nitidipennis (Osella, 1989) comb. n. Puzzling distribution of blind and wingless Mediterranean Absoloniella is briefly discussed.